Apprendre à conseiller, devenir conseiller(ère) - Jonas Masdonati; Koorosh Massoudi (Recherches en Éducation)
The training of career counsellors and vocational psychologists is facing new challenges related to the need to support individuals through multiple career transitions and complex career paths. Anchored on the notions of emerging professionalism (Jorro, 2014) and occupational identity (Brown & Bimrose, 2017) and based on two focus groups with twelve psychology students, we analyzed the learning processes and outcomes of a career counseling training program. Results show a wide range of learning processes (modeling, feedback, practice, and linking theory and practice), leading to the development of technical, intrapersonal and interpersonal skills. They also show that participating in the program stimulates the formation of students’ occupational identity, both in social and personal terms.